PENGARUH PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN MODERASI STRUKTUR MODAL - Jesslin Chandra; Rini Tri Hastuti (Jurnal Paradigma Akuntansi, 2023)
The purpose of this research was to obtain empirical evidence of the effect of profitability and growth on firm value with capital structure as a moderating varible in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The number of samples used in this research were 63 companies that have been tested using the purposive sampling method. Data processing using the software application EViews (Econometric Views) version 12. The result of research indicate that profitability had a significant positive effect on firm value, growth did not have a significant effect on firm value, capital structure was able to moderate and weaken the influence between profitability on firm value, and capital structure cannot moderate the growth on the firm value.